The Challenge of Entrepreneurial Leadership Secondary School Leader in Malaysia - Zuriana Zulkifly; Muhammad Faizal A. Ghani; Faisol Elham (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
This study explores the need to develop an entrepreneurial leadership model for school leaders and identify the challenges faced in practising entrepreneurial leadership in management. A qualitative study design was used to meet the study's aims. The study was conducted through semi-structured interviews with six respondents who were school leaders in Malaysia. The data was analyzed using thematic analysis, where the researcher gave codes to the selected research data to produce themes and research reports. The study findings have found three main challenges school leaders face in implementing entrepreneurial leadership: workload, the leader's knowledge of leadership and the acceptance of organizational members. This study also found several strategies for facing the challenges: effective two-way communication, knowledge sharing, guiding novice teachers (mentors), and support from all levels and facility facilities. The study's implications found that school leaders still need this entrepreneurial leadership model as a leadership guide towards school excellence even though there are challenges in applying the model.